Political Parties, Ideologies, and the Nigerian Economy - EGWIM, Ambose Ihekwoaba (Socialscientia: Journal of Social Sciences and Humanities, 2024)
This paper studied the evolution of ideologies, Nigerian political parties and the economic system - how the development of political parties and ideologies sustained the colonial capitalist economy and governance model. From the independence era in Nigeria (the 1960s) to the current Fourth Republic (1999- ), the ideological transformation of political parties has reinforced the capitalist economy. The argument is that an intimate relationship exists between the developments of Nigerian parties’ ideologies and the Nigerian economic system. Ideology is one of the determinants of the economic system, a driving force in the government’s economic policy-making. Therefore, the nature and ideologies of parties in power shape the country’s economic system. The political parties that have been in power in Nigeria since its inception have helped maintain the status quo - improving the colonial capitalist economy and governance model.